2014
DOI: 10.5194/hessd-11-6441-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What causes cooling water temperature gradients in forested stream reaches?

Abstract: Previous studies have suggested that shading by riparian vegetation may reduce maximum water temperatures and provide refugia for temperature-sensitive aquatic organisms. Longitudinal cooling gradients have been observed during the daytime for stream reaches shaded by coniferous trees downstream of clear cuts or deciduous woodland downstream of open moorland. However, little is known about the energy exchange processes that drive such gradients, especially in semi-natural woodland contexts without confounding … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…A previous work has shown that q radiation may be so reduced within heavily shaded reaches that it no longer dominates the net heat flux (e.g. Garner et al ., ). Considering this result, we hypothesized that for sections of streams that are sufficiently shaded and lacking tributaries, the q radiation and q mixing contributions to ∑ q may be so reduced relative to q convection and q conduction that NLC becomes applicable.…”
Section: Fundamental Physics Of Stream Temperature Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous work has shown that q radiation may be so reduced within heavily shaded reaches that it no longer dominates the net heat flux (e.g. Garner et al ., ). Considering this result, we hypothesized that for sections of streams that are sufficiently shaded and lacking tributaries, the q radiation and q mixing contributions to ∑ q may be so reduced relative to q convection and q conduction that NLC becomes applicable.…”
Section: Fundamental Physics Of Stream Temperature Dynamicsmentioning
confidence: 99%
“…Stream temperature change due to forest harvest has been widely studied at both local scales (e.g. Gray and Edington, ; Brown and Krygier, ; Baillie et al ., ; Gomi et al ., ; Gravell and Link, ; Groom et al ., , ; Janisch et al ., ; Rex et al ., ; DaSilva et al ., ; Kibler et al ., ) and downstream scales (Brown et al ., ; Caldwell et al ., ; Zwieniecki and Newton, ; Story et al ., ; Rutherford et al ., ; Cole and Newton, ; Garner et al ., ; Johnson and Wilby, ). This abundance of studies reflects the concern over stream temperature impacts to aquatic ecosystems and has led to the evolution of stream protection rules for managed forests (e.g.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…River temperature controls are multivariate and nested at regional, sub‐basin, reach or site‐specific scale (Hannah and Garner, ). At regional scale, climate (solar radiation and air temperature) drives the thermal regime of rivers, but at smaller scales, the riparian shading (Moore et al, ) and groundwater inputs could strongly influence the local water temperature (Garner et al, ). However, most of the previous studies have been restricted to the sub‐basin scale or limited to studding the influence of site‐specific factors at a local scale, and there is a lack of research on spatial and temporal variability and controls on river temperature at a regional scale (Hannah and Garner, ).…”
Section: Introductionmentioning
confidence: 99%